Penggunaan model pembelajaran kooperatif tipe round table guna meningkatkan keterampilan menulis puisi peserta didik kelas IV sekolah dasar - Syifana Rizky Normaningtyas Putri; Retno Winarni; Yulianti Yulianti (Didaktika Dwija Indria, 2019)
The purpose of the research is improve the writing skill of poetry by applying the Cooperative Learning Model of Round Table type in grade IV  of  Elementary School of 3 Kalirancang, Alian Sub-district, Kebumen in Academic Year 2018/2019. Classroom Action Research is conducted in two cycles, each cycle consis of  four stages, they are planning, action, observation, and  reflection. The subjects of this study were teachers and  fourth grade students consist 27 students. The data collecting technique are interview, observasion, documentation, and test. The data validity techniqueare content validity and triangultion methods. The data analysis is interactive analysis model (Miles and Huberman). The result of this research, shows that the application of Cooperative Learning Model of Round Table type that can be improve the writing school of poetry. It can be proved by the increasing of the writing poetry skill for each cycle. The percentage of completness in first cycle is 40,74% and increase to 92,59% in second cycle. The conclution of the research is appliying cooperative learning model Round Table type can improve the writing skill of poetry on the IV grade of Elementary School of 3 Kalirancang, Alian Sub-district, Kebumen in Academic Year 2018/2019.Keyword : Cooperative Learning Model Round Table Type,  Writing Skill, Poetry.